The Effect of Company Size, Capital Adequacy, And Level of Funding On Financial Performance Moderated By The Sharia Supervisory Board - Helliana, Helliana; Gunawan, Juniati (Univeristas Islam Bandung, 2023)
This study aims to find out whether the sharia supervisory board moderates the relationship between the variables of company size, capital adequacy, level of funding and financial performance. This study uses hypothesis testing with a quantitative approach. The unit of analysis used in this study is Islamic Commercial Banks in Indonesia (10 Islamic banks). The type of data used is secondary data, data sources from documents obtained through media such as publications or websites. In this study the data used is the Annual Report (Annual Report). Based on the time/time dimension of implementation, this study uses panel data, consisting of 10 Islamic banks in Indonesia, and uses annual data for 8 (eight) periods starting from 2014-2021. The study population was 80. The statistical tools used for panel data analysis were panel regression models, namely Common Effects (CE), Fixed Effects (FE) and Random Effects (RE). Data processing software using Eviews. The findings show that company size and DER have a sizeable impact on financial performance, even though the sharia supervisory board does not moderate the relationship, while the sharia supervisory board moderates the relationship between funding levels and firm performance. The results of this study can be a guideline for managers of sharia banks to provide financing through the most effective level of funding possible. The results of this study can provide a basis for recommending policies to Islamic banking authorities and Islamic banking supervisors in Indonesia.